(untitled) (De Legibus - Law Journal, 2025)
In recent years, a significant and growing number of voices in the literature have questioned the classical criminal politic ambitions of criminal law scholarship. Their efforts to develop a material concept of wrong in order to set limits on the legislature would testify to a radical lack of democratic sensibility. The aim of my contribution is to show that the criticism is based on a misunderstanding of the claims of criminalization thinkers and that criminal law scholarship should continue to question the legitimacy of criminal legislation beyond constitutional limits. In doing so, criminal law scholarship does not arrogate to itself a power to which it is not entitled, but rather makes a crucial contribution to the democratic practice of criminal law.